Introduction - Stéfani, Kelly Cristina; Adames, Mario (Scientific Journal of the Foot & Ankle, 2019)
Dear Colleagues, The Brazilian Association of Medicine and Surgery of the Ankle and Foot (ABTPé) are pleased to present abstract highlights from the ABTPé Biennial Meeting 2019, May 15-18 in Florianopolis, Santa Catarina. The meeting brought together orthopedic foot and ankle surgeons for the purpose of advancing education and research in the Brazil. Although some of the research studies presented at our live conference have been published in the academic literature, many others are not be published. To help bridge the gap between live presentation and publication, the ABTPé selected abstracts (podium presentation, poster, and e-Poster) to publishing in the Scientific Journal of the Foot & Ankle. The Journal offers free and open access to your content on our website. All abstracts are already published with active DOIs. We hope that you enjoy these ABTPé Biennial Meeting 2019 highlights and will find the information useful to your practice. We look forward to meeting you at the ABTPé Biennial Meeting 2021 in Campos do Jordão, São Paulo. Kelly Cristina Stéfani, MD, PHD Associated Editor Scientific Journal of the Foot & Ankle Mario Adames, MD ABTPé Biennial Meeting 2019 President